PRE-TEST AND POST-TEST EVALUATION OF KNOWLEDGE OF “ROLE OF DOCTORS IN SOCIETY” – A FOUNDATION COURSE TOPIC IN 1ST-YEAR MEDICAL UNDERGRADUATE STUDENTS - SRUTHI S; GLORY JOSEPHINE I (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study analyzed the level of improvement in the knowledge about the role of doctors in society using pre-test and post-test models of learning. Methods: The study was conducted in a classroom of 250 1st-year MBBS students. Structured pre-test and post-test questionnaires were designed based on the concept of the foundation course topic “Role of doctors in society” and given at the beginning and end of the class. Results: Out of the 250 1st-year MBBS students, 136 (54.4%) were females and 114 (45.6%) were males. The study revealed that among 250 students, 196 (78.4%) had inadequate knowledge, 51 (20.4%) had moderate knowledge, and only 3 (1.2%) had adequate knowledge in pre-test. After administration of the post-test, 113 (45.2%) had adequate knowledge, 111 (44.4%) had moderate knowledge, and 26 (10.4%) had inadequate knowledge. The paired “t”-test showed a high level of significance (0.001). Conclusion: This study proved the effectiveness of the foundation course topic “Role of doctors in society” in improving the attentiveness and knowledge of the students.